Ranking of Countries according to the Index of Economic Freedom with Multicriteria Decision making Methods - Murat Atan; Sibel Atan; Şahika Gökmen (Athens Journal of Business & Economics)
Every investor wants to conduct their economic or commercial activity in a country with ease. Economic freedom refers to the public limitations that individual or institutional investors must abide by in order to conduct their business. Individual or institutional investors have the chance to produce, consume, and invest more in nations with high levels of economic freedom. If a nation has a high level of economic freedom, it means that institutions and norms are founded and that the economy runs under free market circumstances. Individual or institutional investors are protected and their legal rights are upheld by the public authorities. In this study, the level of tariffs in the country, the presence of restrictions on foreign investments and capital, the black market situation, the taxation system in the country, the presence and importance of the public sector in the economy, the inflation in the country, the country's inflation, and the country's level of tariffs are all taken into account on a country-bycountry basis. The study was conducted by the Heritage Foundation, which has its headquarters in the United States since 1996. Independence of the banking and financial sectors, controls on the prices of products and services and employee wages, regulation and regulation, investor property rights, etc. The data of the "Economic Freedom Index", which consists of fourteen basic criteria including all stages, were examined. This index consists of ten and includes these criteria. With this study, entropy-weighted multi-qualified benefit for the criteria and weights determined in the index calculated by the Heritage Foundation. It aims to provide a fresh option by ranking the "Economic Freedom Index" for all the study's participating nations using the MAUT approach.